2023
DOI: 10.1037/law0000350
|View full text |Cite
|
Sign up to set email alerts
|

Politics or prejudice? Separating the influence of political affiliation and prejudicial attitudes in determining support for hate crime law.

Abstract: Hate crime legislation is a divisive issue in America. While many Americans agree that hate crime laws are necessary, roughly one-third of Americans do not support such legislation. Some research suggests that one reason for this variation in support may be differences in political attitudes. Other research suggests that variation in support may be attributable to differences in prejudicial attitudes toward those minority groups that hate crime laws are intended to protect. Importantly, however, prior research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Specifically, we account for individual assessments of the personal risk respondents believe they face from COVID-19 using a question asking each respondent: “What level of threat do you think COVID-19 poses to you or your family?” This measure was operationalized as a continuous measure, such that higher values indicate higher assessments of risk. Political attitudes, which serve as a proxy for the potential influence of political legitimization in the current study, were measured using an indicator of voting behavior; specifically, respondents were asked the following: “Did you vote in the 2016 Presidential Election?” Respondents then chose from the following options: “yes,” “no,” “don't remember,” or “prefer not to say.” If the respondent answered “yes,” they were then asked: “If so, who did you vote for?” Respondents chose from “Donald Trump,” “Hillary Clinton,” “other candidate,” or “don't know.” This measure was then operationalized as a dummy measure equal to 1 if the respondent indicated they voted for “Donald Trump” and equal to 0 if the respondent indicated they voted for “Hillary Clinton” or “other candidate.” Those who did not vote or refused to share voting information were excluded from the analyses (see Malcom et al, 2022 for a similar approach). Third, we assess the role of information consumption.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we account for individual assessments of the personal risk respondents believe they face from COVID-19 using a question asking each respondent: “What level of threat do you think COVID-19 poses to you or your family?” This measure was operationalized as a continuous measure, such that higher values indicate higher assessments of risk. Political attitudes, which serve as a proxy for the potential influence of political legitimization in the current study, were measured using an indicator of voting behavior; specifically, respondents were asked the following: “Did you vote in the 2016 Presidential Election?” Respondents then chose from the following options: “yes,” “no,” “don't remember,” or “prefer not to say.” If the respondent answered “yes,” they were then asked: “If so, who did you vote for?” Respondents chose from “Donald Trump,” “Hillary Clinton,” “other candidate,” or “don't know.” This measure was then operationalized as a dummy measure equal to 1 if the respondent indicated they voted for “Donald Trump” and equal to 0 if the respondent indicated they voted for “Hillary Clinton” or “other candidate.” Those who did not vote or refused to share voting information were excluded from the analyses (see Malcom et al, 2022 for a similar approach). Third, we assess the role of information consumption.…”
Section: Methodsmentioning
confidence: 99%
“…This measure was then operationalized as a dummy measure equal to 1 if the respondent indicated they voted for "Donald Trump" and equal to 0 if the respondent indicated they voted for "Hillary Clinton" or "other candidate." Those who did not vote or refused to share voting information were excluded from the analyses (see Malcom et al, 2022 for a similar approach). Third, we assess the role of information consumption.…”
Section: Methodsmentioning
confidence: 99%
“…Previous researchers found that Democrats are more likely to take racial discrimination and the threat of COVID-19 more seriously than Republicans (Earle & Hodson, 2020;Taillon et al, 2022). Since racial prejudice functions as a political force and mediates a lower likelihood to support racial hate crime laws (Malcom et al, 2022;Peacock & Biernat, 2022), further examination in future research is needed to study how categorical political affiliations (e.g., Democrats versus Republicans) may mediate negative attitudes toward Asian Americans during the COVID-19 pandemic.…”
Section: Limitations and Future Directionsmentioning
confidence: 93%
“…Hope messages inspire and mobilize voters (Kahn, 1996), as in the case of Barack Obama’s 2008 presidential campaign. On the other hand, hate messages are used, particularly by populist movements (Wu et al , 2022), to exploit fears and prejudices (Malcom et al , 2023). Overall, the use of emotions such as hope and hate in political messaging is a growing area of research that offers insights into the moral values shaping political attitudes and has significant implications for democracy.…”
Section: Theoretical Backgroundmentioning
confidence: 99%